Regulatory frameworks can facilitate or hinder the potential for genome editing to contribute to sustainable agricultural development - Mbaya, Hellen; Lillico, Simon; Kemp, Steve; Simm, Geoff; Raybould, Alan (Frontiers in Bioengineering and Biotechnology, 2022)
The advent of new breeding techniques (NBTs), in particular genome editing (GEd), has provided more accurate and precise ways to introduce targeted changes in the genome of both plants and animals. This has resulted in the use of the technology by a wider variety of stakeholders for different applications in comparison to transgenesis. Regulators in different parts of the world are now examining their current frameworks to assess their applicability to these NBTs and their products. We looked at how countries selected from a sample of geographical regions globally are currently handling applications involving GEd organisms and what they foresee as opportunities and potential challenges to acceptance of the technology in their jurisdictions. In addition to regulatory frameworks that create an enabling environment for these NBTs, acceptance of the products by the public is vitally important. We, therefore, suggest that early stakeholder engagement and communication to the public be emphasized to foster public acceptance even before products are ready for market. Furthermore, global cooperation and consensus on issues cutting across regions will be crucial in avoiding regulatory-related bottlenecks that affect global trade and agriculture.